PERCEIVED SCHOOL CLIMATE, PARENTAL MONITORING AND CYBERBULLYING AMONG ADOLESCENTS - Supe, Inga; Martinsone, Baiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The aim of this research was to find out the connection between the perceived school climate, parental monitoring and cyberbullying among adolescents, and whether there were differences in these variables between two adolescent age groups. It was examined how the dimensions of the perceived school climate and parental monitoring explain the adolescents’ experience of cyber victims and cyberbullies. A total of 309 Latvian students from grades 5 to 12 (200 respondents from grades 5-9 and 109 respondents from grades 10-12) participated in the research. In data collection Parental Monitoring Scale (Stattin & Kerr, 2000), Georgia School Climate Survey (La Salle, McIntosh, & Eliasson, 2016) and European Cyberbullying Intervention Project Questionnaire (Brighi et al., 2012) were applied. The results confirmed significant positive correlation between school climate perception, adequate parental monitoring and less cyberbullying. Also, significant differences between two age groups in perceived school climate, parental monitoring and cyberbullying indications were found. The younger group's adolescents provided more positive evaluations of school climate and parental monitoring, while the older group's adolescents reported more cyberbullying experience. The school climate dimensions Order and discipline, Character, Social support from peers together with negative aspect of parental monitoring Parental solicitation significantly predicted cyberbullying behavior in whole adolescent sample. These results create a better understanding of the variables concerning cyberbullying.